Desain Pengembangan Kurikulum Pendidikan Agama Islam di SD Ditinjau Dari Faktor Teknologi - Nihi Asli (Yayasan Darussalam Bengkulu, 2024)
In recent years, curriculum programs have changed dramatically within Indonesia, as part of a comprehensive reform initiative. The history curriculum for secondary schools was subjected to this transformation as well. This lesson examines the curriculum reform in terms of teacher autonomy, key concepts for understanding and enhancing the role of teachers in education. The study aims to analyze whether the curriculum changes have brought any significant innovations regarding teacher autonomy. The research method used in this article is descriptive analytical. The researcher analyzed related documents, school policies. The research method used in this article is descriptive-analytical. Based on the results of the analysis, that in the face of the times and technology, the design of PAI curriculum development is important. This design must pay attention to the development of the world in order to meet the demands of the times and produce a generation that is technologically literate. The design of the curriculum requires a strong foundation that refers to research and the results of detailed thinking. Curriculum development design that is not based on a strong foundation can trigger the failure of education implementation, which leads to the non-achievement of an educational goal.